Identification of Malay Rattan Properties for Furniture Application - Musa, Noraina Izzati; Mahzan, Shahruddin (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Rattan cane is an important forest product, second only to lumber and bamboo in terms of economic worth and environmental advantages. Mechanical characteristics are more significant quality performance indicators that are highly associated with rattan cane processing and usage. Rattan is a form of natural fibre composite that is broadly employed in a variety of sectors, including architecture and furniture. As a result, it is critical to investigate the mechanical characteristics of rattan to ensure that it is suitable for specific applications. However, in order to tackle the issue of universal mechanical testing and standards on rattan, this present study will discuss the matter by compiling and reviewing researches on the testing methods and results of the mechanical properties of rattan. The testing methods involved are tensile test, bending test and flexural test. Charpy test that is usually used in impact test on rattan furniture is also reviewed in this paper. Conclusion can be drawn that rattan has higher flexural strength when compared with banana fibre, bamboo and steel as rattan is more ductile in nature. It is also exposed that weaving patterns have effects on the rattan seat towards the strength and durability of rattan chairs.